Flexibility of Eukaryotic Okazaki Fragment Maturation through Regulated Strand Displacement Synthesis - Stith, Carrie M. (American Society for Biochemistry and Molecular Biology, 2008)
Okazaki fragment maturation to produce continuous lagging strands in eukaryotic cells requires precise coordination of strand displacement synthesis by DNA polymerase δ (Pol δ) with 5·-flap cutting by FEN1(RAD27) endonuclease. Excessive strand displacement is normally prevented by the 3·-exonuclease activity of Pol δ. This core maturation machinery can be assisted by Dna2 nuclease/helicase that processes long flaps. Our genetic studies show that deletion of the POL32 (third subunit of Pol δ) or PIF1 helicase genes can suppress lethality or growth defects of rad27Δ pol3-D520V mutants (defective for FEN1(RAD27) and the 3·-exonuclease of Pol δ) that produce long flaps and of dna2Δ mutants that are defective in cutting long flaps. On the contrary, pol32Δ or pif1Δ caused lethality of rad27Δ exo1Δ double mutants, suggesting that Pol32 and Pif1 are required to generate longer flaps that can be processed by Dna2 in the absence of the short flap processing activities of FEN1(RAD27) and Exo1. The genetic analysis reveals a remarkable flexibility of the Okazaki maturation machinery and is in accord with our biochemical analysis. In vitro, the generation of short flaps by Pol δ is not affected by the presence of Pol32; however, longer flaps only accumulate when Pol32 is present. The presence of FEN1(RAD27) during strand displacement synthesis curtails displacement in favor of flap cutting, thus suggesting an active hand-off mechanism from Pol δ to FEN1(RAD27). Finally, RNA-DNA hybrids are more readily displaced by Pol δ than DNA hybrids, thereby favoring degradation of initiator RNA during Okazaki maturation.